Cost-effectiveness of culturally-adapted counselling mental distress in low-income ethnic minorities in Hong Kong: results based on a randomized clinical trial - Yi Nam Suen; Yik Chun Wong; Winnie Ng; Shilpa Patwardhan; Charlton Cheung; Stephanie Ming Yin Wong; Christy Lai Ming Hui; Michael Tak Hing Wong; Shalini Mahtani; Eric Yu Hai Chen (SSM - Mental Health)
Introduction: Culturally adapted counselling (CAC) offers a potential solution by delivering culturally tailored early psychological support. However, its cost-effectiveness for reducing mental distress among EMs remains understudied, particularly in Asian settings. This study evaluated the cost-effectiveness of CAC compared to waitlist controls for low-income South Asian EMs experiencing mental distress in Hong Kong, using a healthcare perspective. Methods: This study conducted a trial-based cost-effectiveness analysis (CEA) alongside a randomized clinical trial. A total of 120 participants were randomized into CAC or waitlist groups, with CAC consisting of 6–10 culturally adapted counselling sessions. Costs, including intervention, other mental health service and administrative costs, were calculated using a microcosting approach. The primary outcome was quality-adjusted life years (QALYs), calculated over a 3-month period. Incremental cost-effectiveness ratios (ICERs) were estimated, and cost-effectiveness uncertainty was assessed using bootstrapped cost-effectiveness planes and acceptability curves. Results: CAC resulted reduced cost of other mental health service utilization (adjusted odds ratio [aOR] = 29.67, 95 %CI 23.10, 38.11; p < 0.001) but in greater intervention cost (aOR = 30.14, 95 %CI 23.28, 39.03; p < 0.001) and QALY gains compared to the waitlist group (aOR = 1.50, 95 %CI 1.31, 1,73; p < 0.001). The ICER is HKD 35,088 (USD 4470) per QALY, well below the willingness-to-pay threshold of HKD 385,800 (USD 49,150). Conclusions: CAC is a cost-effective early intervention for EMs experiencing mental distress. Policymakers should consider integrating CAC into community mental health services to address disparities. Future studies should assess long-term cost-effectiveness and strategies to improve male participation.